A new sawfly Cephalcia koreana (Hymenoptera: Pamphiliidae), the pest of Manchurian fir Abies holophylla in Korea - Bia Park; Youngwoo Nam; Cha Young Lee; Seungho Oh; Jong-Kook Jung (Journal of Asia-Pacific Biodiversity, 2023)
The genus Cephalcia Panzer in the sawfly family of Pamphiliidae Cameron is widely distributed in the Holarctic. However, very little is known about the Korean species. Here, we describe Cephalcia koreana Park & Jung, sp. nov. in Korea. Its larvae seriously defoliated leaves of Abies holophylla plantations in Hwacheon-gun, Gangwon Province during 2020–2022. It is newly recognized as an important forest insect pest. We provide taxonomic information including a new key for identifying and separating five Korean species and photographs of diagnostic characters with biological notes and genetic data of the new species.